The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.jneumeth.2015.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Automatic detection of rapid eye movements (REMs): A machine learning approach

Abstract: Background Rapid eye movements (REMs) are a defining feature of REM sleep. The number of discrete REMs over time, or REM density, has been investigated as a marker of clinical psychopathology and memory consolidation. However, human detection of REMs is a time-consuming and subjective process. Therefore, reliable, automated REM detection software is a valuable research tool. New method We developed an automatic REM detection algorithm combining a novel set of extracted features and the ‘AdaBoost’ classificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 64 publications
1
34
0
Order By: Relevance
“…Furthermore the EMG signal helps distinguish REM from W in HCs, but this attribute is often not helpful in the context of RBD, where there can be an absence of atonia in REM. Critical to RBD diagnosis is the identification of REM sleep, and while other studies in automated sleep staging produce better results in REM sleep detection, they benefit from primarily focusing on young HCs or a relatively smaller sample size (Virkkala et al 2008;Güneş et al 2010;Fraiwan et al 2012;Kempfner et al 2012Kempfner et al , 2013bLiang et al 2012;Bajaj and Pachori 2013;Khalighi et al 2013;Imtiaz and Rodriguez-Villegas 2014;McCarty et al 2014;Sousa et al 2015;Lajnef et al 2015;Yetton et al 2016). Despite the lack of sensitivity, REM specificity remains high, which means that as long as REM is identified with a certain precision, the quantified absence of atonia will remain indicative.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore the EMG signal helps distinguish REM from W in HCs, but this attribute is often not helpful in the context of RBD, where there can be an absence of atonia in REM. Critical to RBD diagnosis is the identification of REM sleep, and while other studies in automated sleep staging produce better results in REM sleep detection, they benefit from primarily focusing on young HCs or a relatively smaller sample size (Virkkala et al 2008;Güneş et al 2010;Fraiwan et al 2012;Kempfner et al 2012Kempfner et al , 2013bLiang et al 2012;Bajaj and Pachori 2013;Khalighi et al 2013;Imtiaz and Rodriguez-Villegas 2014;McCarty et al 2014;Sousa et al 2015;Lajnef et al 2015;Yetton et al 2016). Despite the lack of sensitivity, REM specificity remains high, which means that as long as REM is identified with a certain precision, the quantified absence of atonia will remain indicative.…”
Section: Discussionmentioning
confidence: 99%
“…The literature on automated sleep staging describes numerous features, which provided the basis for this study and are summarised in Table 2. For this study the pre-processed EEG, EOG, and EMG signals were segmented into 10 second mini-epochs in order to calculate features for each 30-second epoch, a technique often used for sleep stage classification literature (Güneş et al 2010;Koley and Dey 2012;Liang et al 2012;Lajnef et al 2015;Yetton et al 2016).…”
Section: Feature Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Chapter 4 focuses on the methods and results of P(Sleep) 2.0 and discusses its limitations and possible future directions. Chapters 2 and 3 summarize previous peer-reviewed works by myself (Yetton, McDevitt, Cellini, Shelton, & Mednick, 2018;Yetton et al, 2016), and finer methodological details can be found in their respective papers.…”
Section: Overviewmentioning
confidence: 99%
“…The follow chapter introduces a mathematical model of sleep known as "P(Sleep) 2.0", and combines previous work of the author (a model of sleep architecture known as "P(Sleep) 1.0", and an automatic sleep feature detector, (Yetton et al, 2016)…”
Section: P(sleep) 20 -A Continuous Model Of Sleep Architecture and Fmentioning
confidence: 99%